Applied Pharmacotherapy: Headache And Gout - Ebzal, Kiremzhanov (ScieClouds Publishing, 2023)
This article discusses applied pharmacotherapy related to headaches and Gout. Headache is one of the frequently reported subjective complaints. Based on the causes, they are classified as primary headaches and secondary headaches. The aim of this paper is that students can know the definition of headache, know the classification of panic pain, know the anatomy and physiology of headache, know the prevention of headaches and adjunctive therapy and know the management for headaches.